An Intelligent Recommendation System Utilizing a Hybrid Deep Learning Method - Tholib, Abu; Widiyaningtyas, Triyanna; Prasetya, Didik Dwi (Engineering, Technology & Applied Science Research, 2025)
Recommender systems play a crucial role in enhancing user experience by providing personalized product suggestions, attempting to increase sales and company profitability. However, current methodologies encounter two significant limitations: i) unidirectional models for review information extraction are unable to capture complex contextual semantics effectively, and ii) inefficiency when applied to large-scale datasets. The aim of this research is to develop a novel Hybrid Deep Learning and Probabilistic Matrix Factorization (HD-PMF) model to address the data sparsity problem in recommender systems. This research method is a combination of Bidirectional Long Short-Term Memory (BiLSTM) to capture contextual semantics from user reviews, Stacked Denoising Autoencoder (SDAE) to extract robust latent features from user data, and PMF optimized using Stochastic Gradient Descent (SGD) for accurate rating prediction. The results of this research are based on experiments conducted on two benchmark datasets with high sparsity levels: MovieLens 1M (95.35%) and Amazon Information Video (AIV) (99.98%). The HD-PMF model achieves a Root Mean Square Error (RMSE) of 0.4864, significantly outperforming baseline models such as PMF, Collaborative Deep Learning (CDL), LSTM-PMF, and Dual Deep Learning (DDL)-PMF. These results demonstrate that HD-PMF is an effective and promising approach for improving recommendation accuracy.